Monitoring of Vehicle Exhaust Gases (CO2, NOx, CO) Using Embedded Controller - Jaradat, Yazan; Tahboub, Anas (جامعة بوليتكنك فلسطين - ميكانيك, 2020)
Air pollution is one of the most important problems facing our society, The increase in the number of automobiles day by day is very impending to resolve the problem of air pollution, CO2 emission causes global warming, acid rain and harms the environment This results in the emission of automobile exhaust gases, which are hazardous for human health. Although government forces all cars for testing or examining periodically as the local standard, the actual vehicle on-road emissions are usually much higher than those which are measured during the emission inspections. To realize green traffic, an automated vehicle health monitoring is the need of the day to control the carbon-dioxide emission, there is a need to develop a vehicle engine health monitoring system for early detection of CO2 emission to reduce air pollution. Vehicle Engine Health Monitoring is to develop an embedded system for detecting the vehicle condition by monitoring the internal parameters that are used in evaluating the vehicle’s current health condition. The on-board monitoring equipment consists three gas analyzers for CO, NOx, CO2, which are sensed using gas sensor. The data collected from gas sensor are compared with the standard emission value. Once the emission range varies, the data are transmitted to the control system, and to help the Environment Quantity Authority identify illegal cars and repair their car as soon as possible, which helps in increasing life span of a vehicle and reduce operating cost through efficient combustion process. يعد تلوث الهواء أحد أهم المشكالت التي تواجه مجتمعنا مع زيادة عدد السيارات يوما تلو األخر وهذا يؤدي الى تلوث الهواء بسبب االنبعاثات الصادرة من عوادم السيارات ويؤثر على صحة االنسان والبيئية وتعمل الحكومات على مراقبة نسبة االنبعثات عن طريق اختبارات وفحوصات سنوية ولكن انبعاثات سيارات على الطريق تكون أكثر مما هي موجودة أثناء الفحوصات ومن خالل هذا النظام سنراقب انبعاثات أكاسيد النيتروجين وأول أكسيد الكربون وثاني أكسيد الكربون من خالل مجوعة من السنسور سيتم تثبيتها داخل أنابيب العادم واظهارها بمجرد اختالف نطاق االنبعاث ، يتم نقل البيانات إلى نظام التحكم ، ولمساعدة هيئة .البيئة على تحديد السيارات غير القانونية وإصالح سياراتهم في أسرع وقت ممكن مما يساعد في زيادة العمر االفتراضي للسيارة
no of pages 81 , ميكانيك 12/2020
Keywords: Embedded Controller; Vehicle Exhaust Gases (CO2, NOx, CO)